Kehidupan Akuntan Penyandang Disabilitas dalam Novel Love Risk Management Karya Helen Tanuwan - Risma Dila Agustin; Oktaviana Wahidah; Eva Dwi Kurniawan (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
The problem is that people with disabilities are always considered not to be independent and are often seen as lacking performance in companies. This greatly influences employees with disabilities in adapting to the work environment. Apart from that, the problem raised is the quality of performance of employees who are considered to have committed fraud. The aim of this research is to look at the quality of performance of accountants with disabilities found in literary works. The research method used is the hermeneutical method. The method used is to understand the text and the problem to be able to understand and know the strengths and weaknesses of the text. This research uses data from the literary work used entitled Love Risk Management by Helen Tanuwan. Theories in research are incongruent. The results of this research show that the main character has hearing problems but there are conditions imposed by his former boss so that the main character must be responsible for the bad credit of one of his customers.